Analisa Dan Perancangan Sistem Pendataan Alumni Teknik Informatika Universitas Pamulang Berbasis Web Dengan Metode Waterfall - Monika Juwita; Mochammad Bagoes Satria Junianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the development of an educational institution, alumni have a fairly important role because the role of alumni that can be used as a reflection of the quality of an educational institution itself. But currently there is no container that can be used as a place to manage alumni data, especially in the UNPAM Informatics Engineering study program. Based on these problems, the author wants to create a system that can handle the process of managing alumni data, especially in the UNPAM Informatics Engineering study program. This alumni data collection system is website-based and designed using waterfall and design methods using Undefied Model Language (UML), PHP, using MySQL database server as a database, and using Laravel as its Framework. With this system, a website can be created that can accommodate alumni data of UNPAM Informatics Engineering study program easily, quickly and accurately.